(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to find out the effect of increasing concentrations of sodium chloride and kinetin on some phenotypic and physiological characteristics of barley plant, cultivar Ibaa 99. Two experiments were conducted, the first; Laboratory carried out using a complete random design according to the arrangement of split plates with five replications, and the second in pots according to the design of randomized complete templates and the arrangement of split plates with three replications, where the main factor included five levels of sodium chloride salt (irrigation with distilled water (comparison treatment) and 50, 100, 150 and 200) ml mol/L, while the secondary factor included soaking barley grains with four levels of kinetin (0, 40, 80, and 120) ppm. In both experiments, increasing the sodium chloride level in the irrigation water from 0 to 200 mmol/L led to a decrease in most of the growth and growth characteristics.